CARDIOPROTECTIVE EFFECT OF VITAMIN E AGAINST MYOCARDIAL INFARCTION INDUCED BY ISOPRENALINE IN ALBINO RATS - Abdelhalim, Abdelbaset Taher; Nur, Nuruddin Mohammed; Mansour, Sherif; Ibrahim, Abdelnasser (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Vitamin E is an antioxidant which can help in the prevention of cardiovascular disease. The objective of this study was to estimate the effects of Vitamin E on cardiac marker enzymes in isoprenaline (ISO)-induced myocardial infracted rats. Methods: Adult male albino rats were divided into three groups. The first group was the control negative group. The second group was the control positive group that was subcutaneously injected with ISO (100 mg/kg). The third group was pretreated with Vitamin E (100 mg/kg) once daily for 30 days, then subcutaneously injected with ISO at an interval of 24 h for 2 days. Aspartate aminotransferase (AST), alanine transaminase (ALT), lactate dehydrogenase (LDH), cardiac troponin-I (CTn-I), glutathione (GSH), superoxide dismutase (SOD), malondialdehyde (MDA), and histopathological examinations were measured. Comparison between groups was achieved by one-way analysis of variance (ANOVA) test through SPSS software. Results: The levels of AST, ALT, LDH, creatine kinase (CK), and CTn-I significantly decreased in pretreated group with Vitamin E compared to its increasing in the control positive group. The level of GSH and SOD markedly increased in pretreated group with Vitamin E compared to its decreasing in the control positive group, while the level of MDA significantly decreased in pretreated group with Vitamin E compared to its increasing in the control positive group. ISO + Vitamin E rats group reflected a cardioprotective role of Vitamin E in myocardial infarcted rats. Conclusion: Pretreatment with Vitamin E can protect the myocardial membranes against ISO-induced oxidative stress in rats and can be used for routine clinical and epidemiological purposes.